The social and economic effects of consumer-oriented food subsidies: a summary of current evidence - Pinstrup-Andersen, Per (International Food Policy Research Institute, 1988)
The social and economic effects of consumer-oriented food subsidies are wide ranging. While the immediate purpose may be relatively narrow—for example, assuring some or all consumers access to a given quantity of food at prices fixed by the government—the effects of subsidies may be felt in a variety of ways both at the household level and throughout the economy. This chapter presents an overview of the most important potential effects in order to provide a framework for the rest of the book and summarizes the most significant empirical findings regarding these effects. The policy implications of the findings are discussed throughout the book and are summarized in chapters 23 and 24.